Structural characterization of polysaccharides from Cabernet Franc, Cabernet Sauvignon and Sauvignon Blanc wines: Anti-inflammatory activity in LPS stimulated RAW 264.7 cells. (15th April 2018) - Bezerra, Iglesias de Lacerda; Caillot, Adriana Rute Cordeiro; Palhares, Lais Cristina Gusmão Ferreira; Santana-Filho, Arquimedes Paixão; Chavante, Suely Ferreira; Sassaki, Guilherme Lanzi
Highlights: Sauvignon Blanc, Cabernet Sauvignon and Cabernet Franc wines have different polysaccharides. The wines have Mannan, AGII, RGI and RGII and anti-inflammatory activity. Mixture and isolated polysaccharides inhibited the production of TNF-α, IL-1β and NO. Abstract: The structural characterization of the polysaccharides and in vitro anti-inflammatory properties of Cabernet Franc (WCF), Cabernet Sauvignon (WCS) and Sauvignon Blanc (WSB) wines were studied for the first time in this work. The polysaccharides of wines gave rise to three fractions of polysaccharides, namely (WCF) 0.16%, (WCS) 0.05% and (WSB) 0.02%; the highest one was chosen for isolation of polysaccharides (WCF). It was identified the presence of mannan, formed by a sequence of α-d -Man p (1 → 6)-linked and side chains O -2 substituted for α-d -mannan (1 → 2)-linked; type II arabinogalactan, formed by (1 → 3)-linked β-d -Gal p main chain, substituted at O -6 by (1 → 6)-linked β-d -Gal p side chains, and nonreducing end-units of arabinose 3- O -substituted; type I rhamnogalacturonan formed by repeating (1 → 4)-α-d -Gal p A-(1 → 2)-α- L -Rha p groups; and traces of type II rhamnogalacturonan. The polysaccharide mixture and isolated fractions inhibited the production of inflammatory cytokines (TNF-α and IL-1β) and mediator (NO) in RAW 264.7 cells stimulated with LPS.